IMPLEMENTASI PENDIDIKAN KARAKTER MAHASISWA JURUSAN KEBIDANAN POLTEKKES. SEMARANG, TAHUN 2015 - Ngadiyono Ngadiyono; Bahiyatun Bahiyatun; Titi Suherni (JURNAL KEBIDANAN, 2016)
The study aims to describe the character education, and the results are expect- ed to be useful theoretically and practically in the development of character education.               Concurrent method using mixed methods research, design, sequential explanatory designs, which collects qualitative data was first performed and analyzed by content analysis in accordance stages.               Results of the survey respondents' choice of the base value, respectively, the value of religiosity, peaceloving, hard work, discipline, responsibility, and to be honest, caring social and communicative. In terms of implementation, planning, through a program that is still separate, formulated by the Court subject to the specific, stand-alone activity dilaksanan between curricular, co-curricular and extra. While the evaluation and assessment through quantitative assessment of the knowledge element.            In conclusion, the educational value of these characters, do not yet have clear arguments, then in terms of the planning, implementation and evaluation have not been integrated. Given the importance of a value, for students, it would require more research is needed lanjud and policy / program from stakeholders